2014
DOI: 10.3892/or.2014.3361
|View full text |Cite
|
Sign up to set email alerts
|

Diallyl disulfide induces G2/M arrest and promotes apoptosis through the p53/p21 and MEK-ERK pathways in human esophageal squamous cell carcinoma

Abstract: Abstract. Esophageal squamous cell carcinoma (ESCC) is an aggressive tumor with high incidence and mortality worldwide. Diallyl disulfide (DADS) is a natural organosulfur compound, isolated from garlic. In this study, MTT assay showed that DADS significantly reduced cell viability in a dose-and timedependent manner in ESCC cells, with lower toxicity in normal liver cells. Cell cycle analysis revealed that DADS made G2/M phase arrest. Molecular analysis suggested that this cell cycle arrest was likely made by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 26 publications
1
36
0
Order By: Relevance
“…31 Some studies have reported that ERK-or JNK/MAPK activation induces G2/M phase arrest and apoptosis in solid tumors. [32][33][34][35][36] We found that palbociclib destabilizes HIF-1a and activates ERK1/2 under either normoxic or hypoxic conditions (Fig. 3).…”
Section: Discussionmentioning
confidence: 78%
“…31 Some studies have reported that ERK-or JNK/MAPK activation induces G2/M phase arrest and apoptosis in solid tumors. [32][33][34][35][36] We found that palbociclib destabilizes HIF-1a and activates ERK1/2 under either normoxic or hypoxic conditions (Fig. 3).…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies have demonstrated that oncogenes, such as p53, c-Myc, matrix metallopepti- dase 9 and human sterile alpha motif domain-containing 9, are abnormally expressed in ESCC tissues (22)(23)(24). Furthermore, increased expression levels of transforming growth factor-β may stimulate the PTEN/PI3K pathway and promote epithelial-mesenchymal transition in the human esophageal epithelium (25).…”
Section: Discussionmentioning
confidence: 99%
“…G 2 /M phase arrest was induced by diallyl disulfide by decreasing cyclin B1, CDC2, p-CDC2 and cdc25c, and activating the p53/p21 pathway. Apoptosis was induced by diallyl disulfide through activation of caspases, alteration of Bax/Bcl-2 balance and suppression of the MEK-ERK pathway [151]. The results were also verified in human esophageal carcinoma ECA109 cells and in mice [152].…”
Section: Garlicmentioning
confidence: 97%